VIOLATIONS OF HUMAN RIGHTS, USE OF CHEMICAL WEAPONS AND THE PHENOMENON OF “NON-STATE ACTORS”: A REFLECTION ABOUT THE U.N. SECURITY COUNCIL RESOLUTIONS RELATED TO SYRIA (2016)
The study suggests a reflection on the UN Security Council resolutions issued between 2013 and 2015 about the conflict in Syria. It offers a critical analysis of the various issues covered by the Security Council, mainly the related to the violation of human rights, the use of chemical weapons and terrorism. The analysis takes into account the main doctrinal theories of international law related to the three main arguments treated with a reflection oriented to the analysis of the phenomenon of “non- State actors” playing on the Syrian scenario. Those actors, which have been firstly considered as internal rebel groups, secondly treated as terrorist groups, escalated in the last period of the conflict into a peculiar entity which threatens the international community acting as a “para-State” searching for a dangerous sort of legitimation. In view of this risk, the response of the UN Security Council has been uncertain so far and paved the way for new and serious challenges for the international community which are highlighted by the article.